The estimate of protein polymorphism in human populations: lack of evidence for overestimation due to post-translational modification - FERRELL, Robert E.; FUERST, Paul A. (Japanese journal of genetics, 1985)
New sensitive population screening procedures, such as isoelectric focusing, enzyme activity assays and the use of multiple electrophoretic conditions have uncovered considerable hidden variation at many structural loci. It has been suggested, however, that a significant portion of the newly identified variation is due to alleles at modifier genes which cause the post-translational modification of the structural gene product. Some investigators have questioned whether genetic variability assigned to structural loci in Drosophila has been greatly overestimated because of a failure to recognize the existence of such polymorphic modifier genes. Data from human populations has been reviewed for evidence of such genetically mediated posttranslational modification (GMPTM). Tnree genetic systems (glucose-6-phosphate dehydrogenase, alpha-1-antitrypsin and hemoglobin) are reviewed in detail. Each system is subject to non-genetic post-translational modification, but none of the data currently available indicates any role of GMPTM. Other data, including studies on null alleles, activity variants, population surveys and somatic cell hybrids is also reviewed. Again, no convincing evidence has been uncovered for the presence of GMPTM. It is concluded that the current estimates of polymorphism for enzymes and structural proteins in human populations have not been inflated due to the presence of polymorphism for modifier loci.